Pendidikan Antikorupsi untuk Generasi Muda: Menanamkan Nilai-Nilai Antikorupsi Sejak Dini - Theofilus Silitonga (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
As agents of change, young people require the important role of education in shaping their character and behavior from an early age. The eradication of corruption cannot be carried out solely through law enforcement but also needs to be addressed through education as a preventive measure. Anti-corruption education plays a crucial role in instilling values of honesty, discipline, responsibility, and integrity from a young age. As the nation’s future successors, young people hold a strategic role as agents of transformation; therefore, the development of integrity-based character is essential. Through the strengthening of effective governance systems, continuous character education, and strict law enforcement, it is expected that a generation with integrity will emerge one that is capable of rejecting corrupt practices in order to realize a just, prosperous, and corruption-free society.